Methods for Cell-attached Capacitance Measurements in Mouse Adrenal Chromaffin Cell - Varga, Kelly T. (J Vis Exp, 2014)
Neuronal transmission is an integral part of cellular communication within the brain. Depolarization of the presynaptic membrane leads to vesicle fusion known as exocytosis that mediates synaptic transmission. Subsequent retrieval of synaptic vesicles is necessary to generate new neurotransmitter-filled vesicles in a process identified as endocytosis. During exocytosis, fusing vesicle membranes will result in an increase in surface area and subsequent endocytosis results in a decrease in the surface area. Here, our lab demonstrates a basic introduction to cell-attached capacitance recordings of single endocytic events in the mouse adrenal chromaffin cell. This type of electrical recording is useful for high-resolution recordings of exocytosis and endocytosis at the single vesicle level. While this technique can detect both vesicle exocytosis and endocytosis, the focus of our lab is vesicle endocytosis. Moreover, this technique allows us to analyze the kinetics of single endocytic events. Here the methods for mouse adrenal gland tissue dissection, chromaffin cell culture, basic cell-attached techniques, and subsequent examples of individual traces measuring singular endocytic event are described.